COST AND ACCESSIBILITY RELATED FACTORS INFLUENCING THE SELECTION OF AREAS OF RESIDENCE IN KENYA: A SURVEY OF NAIROBI RESIDENTS - Kahura, Grace W. Njoroge; Kamaria, Prof. Joe K. (International Journal of Finance, 2017)
Purpose: The purpose the study was to investigate the cost and accessibility related factors influencing the selection of areas of residence in Kenya in the case of Nairobi residents. Methodology: The researcher used descriptive research design. The scope of the study was limited to Nairobi County. The study identified a population of 985,016 households in Nairobi County out of which a sample of 150 respondents were used. Random sampling technique was used to select the respondents from each category. The study used primary data that was collected using questionnaires. Data was analyzed using Statistical Package for Social Sciences (SPSS). The data was then analysed in terms of descriptive statistics like frequencies and percentages. Results: The results indicated that majority of the respondents found economic and accessibility factors as being important while choosing their places of residence. The results indicated that the most important economic factor is income, followed by transfer costs, cost of living, price, and transport costs. Ease of qualifying for a mortgage, availability of mortgage, ease of qualifying for a mortgage, maintenance costs were least ranked. The study also found that the most important accessibility factor was road network, followed by water, nearness to workplace, parking space, health centers, internal space, and electricity, and transport costs. The least ranked factors were drainage, parks and open spaces, availability of garden, and floor plans. Unique contribution to theory, practice and policy: The study recommended that cost related factors such as cost of living among others should be given a priority when making a decision on where to reside since such economic related factors touch on one's disposable amount. It is also recommended that it would be significant for landlords to put into consideration such economic factors before concluding on either the rent prize or the prize of a piece of land since their potential tenants' or buyers' decision is most likely to be influenced by such factors. It is also recommended that landlords should put into consideration accessibility factors before building rental houses. Such factors as road network are very important and will obviously influence the tenants' decision on residing in a certain area.